Yusif Hadi - Koyukuo village (Lawra District), Ghana - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Yusif Hadi is a dedicated cattle and agriculture farmer from the village Koyukuo in Ghana. He talks about by the lack of rainfall, the consequences on the animal feed and how they are changing the feeding habits of the heard supplementing the fodder with maize husks and groundnut tops. Another way that Yusif has adapted to the changes in the climate and lack of rain is by planting maize that grows in three months instead of the regular four months.